2019
DOI: 10.2147/ott.s191736
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical efficacy and survival analysis of apatinib combined with docetaxel in advanced esophageal cancer</p>

Abstract: Background and aim Standard chemotherapy has limited clinical efficacy in patients with esophageal cancer and there is a significant and unmet clinical need for effective treatment options for these patients. The aim of this study was to compare the clinical efficacy of the novel, targeted drug apatinib combined with docetaxel, and docetaxel combined with S-1 as second- or further-line treatment for patients with advanced esophageal cancer. Methods We enrolled 33 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…In our study, we discovered that high VEGFR2 associated with poor clinical efficacy of cisplatin-based chemotherapy in advanced esophageal cancer. Existing clinical studies have shown that apatinib causes some adverse reactions, such as hypertension, hand and foot syndrome, proteinuria, diarrhea, and the incidence of adverse reactions are increased with the combination of regular dose of apatinib and chemotherapy [17,44]. Data from a clinical study have demonstrated that low dose apatinib plus chemotherapeutic agent is effective without increasing adverse reactions in lung cancer [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we discovered that high VEGFR2 associated with poor clinical efficacy of cisplatin-based chemotherapy in advanced esophageal cancer. Existing clinical studies have shown that apatinib causes some adverse reactions, such as hypertension, hand and foot syndrome, proteinuria, diarrhea, and the incidence of adverse reactions are increased with the combination of regular dose of apatinib and chemotherapy [17,44]. Data from a clinical study have demonstrated that low dose apatinib plus chemotherapeutic agent is effective without increasing adverse reactions in lung cancer [45].…”
Section: Discussionmentioning
confidence: 99%
“…At present, a series of clinical trials of apatinib have been conducted and achieved improved clinical efficacy in multiple cancers, such as digestive tract cancer, breast cancer and lung cancer [10][11][12][13][14][15]. Few clinical retrospective studies have preliminarily suggested that apatinib alone or in combination with chemotherapy is efficacious for advanced esophageal cancer as a secondline or later treatment [16,17]. However, the possible function and mechanism of apatinib in the treatment of esophageal cancer is still poorly understood.…”
mentioning
confidence: 99%
“…Apatinib is a novel inhibitor of angiogenesis that targets the intracellular adenosine triphosphate-binding site of VEGFR2 [12]. Apatinib has shown positive results as a second-or further-line treatment in patients with ESCC [13][14][15][16]. The overexpression of VEGF in esophageal cancer may be associated with a poor prognosis [17,18].…”
Section: Study Completedmentioning
confidence: 99%
“…Apatinib has been demonstrated to have promising activity against gastric, breast, and lung tumors [12]. Moreover, a retrospective analysis concluded that apatinib (500 mg daily) combined with docetaxel may be effective as a second-line treatment for advanced esophageal cancer, with a median PFS of nearly 6 months, an ORR of 88.9%, and a DCR of 93.3% [14]. However, very few previous studies have explored the use of © AlphaMed Press 2020 Apatinib Monotherapy for Advanced Esophageal Cancer e1468 apatinib monotherapy in the setting of advanced cancer of the esophagus or gastroesophageal junction.…”
Section: Study Completedmentioning
confidence: 99%
“…61 Studies of apatinib combined with docetaxel for advanced ESCC have revealed that this combination therapy can be used as secondline or further treatment for patients with advanced ESCC. 62 Anlotinib. Anlotinib is a small-molecule inhibitor that can act on multiple targets.…”
Section: Targeting Key Signaling Pathwaysmentioning
confidence: 99%